Magnetostriction studies on transition metal substituted cobalt ferrite - Bhame, D. Shekhar; Bhapkar, Abhishek; Shirolkar, Mandar M.; Joy, Pattayil A. (Journal of the Indian Chemical Society, 2022)
Structural, magnetic and microstructural properties of transition metal (TM) substituted cobalt ferrite Co0.9TM0.1Fe2O4 (where TM = Ti, Cr, Mn, Ni and Cu and Zn) were investigated. The present study shows marked dependence of the magnetostriction on the concentration of the substituted transition metal ions for Cobalt in CoFe2O4. The magnetic characteristics of the prepared compositions such as coercivity, anisotropy constant and saturation magnetization changed significantly on transition metal substitution. The present study shows the way to tune the anisotropy of cobalt ferrite by effective substitution of other transition metal ions for Co which subsequently affects the stress sensing performance by changing the slope of the magnetostriction curve. Apart from the magnetic properties the microstructure can also be effectively modified by substitution of other transition metal ions. Only 10% substitution of cobalt showed drastic influence on magnetostriction and slope of magnetostriction curve. The composition with 10% nickel Co0.9Ni0.1Fe2O4 exhibited maximum slope for the magnetostriction curve of -53.7 ppm/Oe, along with reasonably high magnitude of strain of 186 ppm making it a suitable for exploring stress sensing applications.
Keywords: Ferrite; Magnetoelastic; Magnetostriction; oxide; stress sensing